Studi Empiris: Tax Avoidance pada Perusahaan non Keuangan di Bursa Efek Indonesia - Aristyo Rahadiyan Tedja; Novia Wijaya (Media Bisnis, 2022)
The purpose of this study is to obtain empirical evidence regarding the effect of the proportion of independent commissioners, audit committee, audit quality, profitability, firm size, institutional ownership and leverage on tax avoidance. Previous researchers used 5 variables, namely the proportion of independent commissioners, audit committee, audit quality, profitability, and firm size. This researcher adds 2 variables, namely institutional ownership and leverage. This study obtained research samples using purposive sampling method. There are 396 data from 132 non-financial companies listed on the Indonesia Stock Exchange for the 2017-2019 period that have met the criteria. The multiple regression method is a model of this research. The results of this study indicate that profitability and leverage have a significant effect on tax avoidance, while other independent variables such as the proportion of independent commissioners, audit committee, audit quality, firm size and institutional ownership do not have a significant effect on tax avoidance. The larger the profit generated, the company will get tax incentives and tax concessions so that it appears to be doing tax avoidance. The larger the debt the company uses as financing, the interest expense that must be paid. The higher the interest expense, the lower the profit so that tax avoidance will be lower.